2014
DOI: 10.1603/en13263
|View full text |Cite
|
Sign up to set email alerts
|

Population Dynamics ofScirtothrips dorsalis(Thysanoptera: Thripidae) and Other Thrips Species on Two Ornamental Host Plant Species in Southern Florida

Abstract: Since its 2005 introduction into the United States, chilli thrips, Scirtothrips dorsalis Hood (Thysanoptera: Thripidae), has become a problematic pest of agronomic, vegetable, fruit, and ornamental plants. Knowledge of its population dynamics may help managers better monitor and control S. dorsalis. Population estimates were recorded for S. dorsalis and other thrips species on Knock-Out rose (Rosa 'Radrazz') and green buttonwood (Conocarpus erectus L.) from July 2007 to September 2008 in two field plots (one p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…This finding suggested initial, random colonization events followed by gradual, more local population growth and expansion to adjacent plants (Seal et al 2006). Mannion et al (2014) compared buttonwood with rose (but not schefflera) and found more S. dorsalis nymphs on rose than on buttonwood plants, but the percentage of the population that was adult appeared larger on buttonwood. Similarly, in the present study, S. dorsalis densities and damage ratings were lower on buttonwood than on schef-flera suggesting the latter may be a better host plant species for survival and reproduction of S. dorsalis.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This finding suggested initial, random colonization events followed by gradual, more local population growth and expansion to adjacent plants (Seal et al 2006). Mannion et al (2014) compared buttonwood with rose (but not schefflera) and found more S. dorsalis nymphs on rose than on buttonwood plants, but the percentage of the population that was adult appeared larger on buttonwood. Similarly, in the present study, S. dorsalis densities and damage ratings were lower on buttonwood than on schef-flera suggesting the latter may be a better host plant species for survival and reproduction of S. dorsalis.…”
Section: Discussionmentioning
confidence: 95%
“…According to Mannion et al (2014), a greater diversity and abundance of thrips (including S. dorsalis) was found on or near rose than on or near buttonwood plants. Higher numbers and densities of S. dorsalis were found on rose than on buttonwood throughout the year suggesting rose is a more attractive (or less repelling) host plant species (Mannion et al 2014). At least 19 thrips species including S. dorsalis were found on plants and in traps on or near Knock-Out® rose or green buttonwood plants (Mannion et al 2014).…”
mentioning
confidence: 99%
“…In this study, this species was found in an average temperature of 24.4°C in all ecological regions, which means an advantageous condition for its establishment. Additionally, S. dorsalis density has been positively correlated with temperature but negatively correlated with relative humidity and precipitation ( Mannion et al 2014 ). Because the Andean and Caribbean regions are characterized by a bimodal precipitation regimen with changing seasonal average temperatures, but Orinoquia regions have a monomodal rain regime between April and November with more constant average temperature throughout the year ( Pacheco and León-Aristizabal 2001 ), we expect that geographical dispersion and establishment of S. dorsalis will be differential for these three regions.…”
Section: Discussionmentioning
confidence: 99%
“…indica and M. pudica and could not be proven by this study. Nevertheless, weeds surrounding main host could serve as alternate host and serve as a potential reservoir and pathway for thrips moving to preferred hosts (Mannion, Derksen, Seal, Osborne, & Martin, 2014;Song, Kim, Yang, Hong, & Lee, 2013). Aliakbarpour & Md Rawi (2011) indicated that weeds surrounding the canopy of mango were utilized by thrips S. dorsalis as alternate host in pesticide high input and low input orchard.…”
Section: Population Dynamic In High Input Blockmentioning
confidence: 99%